Platinum plus bortezomib for the treatment of pediatric renal medullary carcinoma: Two cases. Issue 7 (4th January 2017) - Carden, Marcus A.; Smith, Stephen; Meany, Holly; Yin, Hong; Alazraki, Adina; Rapkin, Louis B.
Abstract: Renal medullary carcinoma (RMC) was first described over two decades ago as the seventh sickle nephropathy. Survival after diagnosis with metastatic disease still rarely extends beyond 1 year, with recent reports of median overall survival in patients treated with platinum therapy being just 10 months. We describe our experience using platinum‐based chemotherapy plus the proteasome inhibitor bortezomib to treat metastatic RMC in two pediatric patients who had complete responses. One patient passed away 7 years after diagnosis, while another remains disease free nearly 2 years from diagnosis.